High‐Electric‐Field‐Induced Phase Transition and Electrical Breakdown of MoTe2. (27th January 2020) - Kim, Changsik; Issarapanacheewin, Sudarat; Moon, Inyong; Lee, Kwang Young; Ra, Changho; Lee, Sungwon; Yang, Zheng; Yoo, Won Jong
Abstract: 2D molybdenum ditelluride (MoTe2 ) has recently received significant attention due to its unique phase transition and ambipolar behavior as well as thickness‐dependent bandgap. The phase transition and electrical breakdown of various thickness MoTe2 field‐effect transistors observed under high electric fields are addressed. Interestingly, the MoTe2 exhibits phase transition from a semiconducting 2H phase to a metallic 1T′ almost simultaneously with electrical breakdown, and this is confirmed by a Raman peak of 1T′‐MoTe2 at 125 cm −1 . Using Raman mapping results of MoTe2 FETs obtained after the breakdown, it is revealed that the phase transition is initiated from the metal contacting electrode regions of source and drain. All the Raman peaks of MoTe2 shifted to low frequency with increasing drain voltage. Based on the Raman peak shifts, the temperature change in the MoTe2 FETs while device operation is in progress is estimated. The maximum temperature and dissipated power of a tri‐layer MoTe2 device are found to reach 495 K and 5.85 mW, respectively, at an electric field of 6.5 V µm −1 . This research provides guidelines for circuit design toward the application of 2D semiconductor devices, related to the energy dissipation and electrical breakdown unique to 2D phase transitional materials. Abstract : The phase transition of molybdenum ditelluride (MoTe2 ) from a semiconducting 2H phase to a metallic 1T′ phase is observed together with its electrical breakdown under high electric field. Raman spectroscopy mapping results confirm the phase transition from various thicknesses of MoTe2 .